The double-edged sword effects of active social media use on loneliness: The roles of interpersonal satisfaction and fear of missing out - Mao, Jian; Fu, Ge-xi; Huang, Jian-jun (Frontiers in Psychology, 2023)
Introduction Social media' impact on loneliness has attracted widespread scholarly attention. One hypothesis is that active social media use (ASMU) is associated with a decrease in loneliness. However, several empirical studies did not find a significant correlation between ASMU and loneliness, and ASMU may even increase loneliness. This study explored the mechanism of the double-edged sword effects of ASMU on loneliness. Methods Data were collected through convenience sampling from three universities in China. A total of 454 Chinese college social media users (Mean age 19.75 ± 1.33; 59.92% female) completed an online questionnaire. Results ASMU was positively related to interpersonal relationship satisfaction, which was negatively related to general trait-fear of missing out (FoMO) and loneliness. Further structural equation modeling (SEM) analysis showed that ASMU could negatively predict loneliness through the mediation pathways of interpersonal satisfaction and “Interpersonal satisfaction → Trait-FoMO.” At the same time, ASMU was also positively associated with online-specific state-FoMO, which was positively associated with trait-FoMO and loneliness. Further SEM analysis found no mediation effect of state-FoMO between ASMU and loneliness, but state-FoMO and traitFoMO sequentially mediate the relationship between ASMU and loneliness. Discussion This study indicates that ASMU may increase and decrease loneliness. Interpersonal satisfaction and FoMO explained the double-edged mechanism of ASMU on loneliness. These findings contribute to dialectically understanding the effectiveness of active social media use and provide theoretical guidance for promoting the beneficial aspects of social media while weakening its harmful consequences.